Optimization of agitation and aeration conditions in bench-top scale stirred-tank bioreactor for maximum L-Dopa production - Peralta, Maria Patricia (2021)
The main success of a bioreactor is simulating environmental conditions which are favorable for microbial growth, as well as for the secretion of enzymes and the production of further metabolites. Therefore, the bioprocess development requires to optimize the conditions under which this bioreactor is operated. As the volume scale is raised, aeration and agitation conditions become more compromised, so their optimization is a must. The objective of this work was to study the influence of aeration and agitation conditions during L-Dopa production at bench-top bioreactor scale by using the Paraboeremia LY 38.7 fungal isolate selected from Las Yungas Tucumanas. First, operative conditions of aeration (1 vvm), temperature (25 °C) and pH (pHi = 7) were kept constant, whilst varying agitation parameter between 250, 200 and 150 rpm. Once the agitation parameter was optimized, different aeration values were evaluated (0.5, 1.0 and 1.5 vvm). Production of L-Dopa and consumption of L-Tyrosine were measured by means the Arnow method, tyrosinase monophenolase and diphenolase activities according to the dopachrome method, and biomass was estimated as dry weight. From the set of tested conditions, an agitation speed of 200 rpm and an airflow rate of 1.0 vvm allowed obtaining the highest L-Dopa production (229,04 mg·L-1) in 56 h. At the higher aeration value (1.5 vvm) L-Dopa production became decreased (162,69 mg·L-1), and the same happened at the higher agitation set point (107,94 mg·L-1), along with the production of a polymer. At lower agitation and aeration, less production of L-Dopa (94,57 mg·L-1 and 130,94 mg·L-1) was found as well as less fungal growth, so that the decrease in production could be due to a lower biosynthetic machinery which depends on biomass. Selected conditions would be advantageous from the operational point of view, particularly considering the subsequent bioprocess scale-up, since they would imply lower operating costs.